INTEGRATING GAMIFICATION STRATEGIES WITH VR/AR: ANALYZING THE RESULT OF EXPERIMENTAL ARCHITECTURAL STUDIO IN PAKISTAN - Quratulain Asghar; Fatima Javeed (International Journal of Contemporary Issues in Social Sciences, 2024)
This study reflects upon integrating Gamification in Architecture using Virtual and Augmented reality (VR/AR) through studio pedagogy in Pakistan. It emphasizes the role of gamification in addressing the challenges of contemporary studio teaching, which needs to be updated with interactive and participatory design techniques. Game-based learning effectively incorporates spatial awareness, immersive interaction, and a collaborative environment that aligns with contemporary architectural studio requirements. The study highlights the outcomes of two studio projects from the Fall semester of 2023 conducted with 4th-year students from the Architecture Department at the University of Engineering and Technology Lahore: one involves redesigning Lahore’s Liberty Market into a car-free zone, and the other simulates an alteration between a dystopian landscape and a solar-powered utopia to influence design choices. These projects are crucial for understanding the role of gamification in Architecture. The main challenges during the fourteen-week-long studio included the steep learning curve associated with new tools and technologies, including using Unreal Engine, a gaming software. Even with these hurdles, the research shows gamification as a promising approach for the future of architectural education. It posits that incorporating gamified VR/AR can significantly enrich the curriculum. The exploration led to the development of a robust design and collaboration skills essential for adapting to the changing architectural environment. The research paper suggests that cross-reality gamification has the potential to impact academic practices and, subsequently, the wider architectural profession, promoting a more involved, technologically adept, and environmentally conscientious approach to design.